WIDESPREAD BACTERIAL POPULATIONS AT GLACIER BEDS AND THEIR RELATIONSHIP TO ROCK WEATHERING AND CARBON CYCLING - Sharp M.; Parkes J.; Cragg B.; Fairchild I.J.; Lamb H.; Tranter M. (My University, 1999)
Bacterial populations found in subglacial meltwaters and basal ice are comparable to those in the active layer of permafrost and orders of magnitude larger than those found in ice cores from large ice sheets. Populations increase with sediment concentration, and 5% 24% of the bacteria are dividing or have just divided, suggesting that the populations are active. These findings (1) support inferences from recent studies of basal ice and meltwater chemistry that microbially mediated redox reactions may be important at glacier beds, (2) challenge the view that chemical weathering in glacial environments arises from purely inorganic reactions, and (3) raise the possibilities that redox reactions are a major source of protons consumed in subglacial weathering and that these reactions may be the dominant proton source beneath ice sheets where meltwaters are isolated from an atmospheric source of CO2. Microbial mediation may increase the rate of sulfide oxidation under subglacial conditions, a suggestion supported by the results of simple weathering experiments. If subglacial bacterial populations can oxidize and ferment organic carbon, it is important to reconsider the fate of soil organic carbon accumulated under interglacial conditions in areas subsequently overridden by Pleistocene ice sheets.
Keywords: Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен